The importance of speech therapy technology in the education of children with speech disabilities (Eurasian Journal of Learning and Academic Teaching, 2022)
The elimination of underdevelopment is relevant in modern speech therapy is one of the problems. This is of great practical importance: the speech is complete early detection of underdeveloped children and timely correction work to prevent and eliminate children's backwardness in learning their mother tongue important in maturation. There is a number of research areas in this area conditioned by factors.